ANALISIS KARAKTERISASI XRD SINTESIS MATERIAL La0,7Ca0,3(Mn,Co)O3 MELALUI METODE MECHANICAL ALLOYING - Anggita Prasanti; Riser Fahdiran; Sitti Ahmiatri Saptari; Erfan Handoko (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
Perovskite manganites materials La0,7Ca0,3Mn1-xCoxO3 with x = 0 and x = 0.1 through mechanical alloying method to characterize x-ray difraction has been synthesized. Material consisting of La2O3, CaO, MnCO3, and Co3O4 mixing by high energy ball mill for 1 hour and produce a homogeneous mixture followed by calcination at 750 Â° C and molding sample pellets and sintering at 1100 Â° C for 3 hours and monoclinic crystal structure with lattice parameters for x = 0 a = 7.752 Ã…; b = 5.463 Ã…; c = 5.466 Ã… and 231.54 A3 cell volume with 39.27 nm crystal size and density Ï = 6.93 g / cm3, while for x = 0.1 a = 7.742 Ã…; b = 5.470 Ã…; c = 5.460 Ã… and 231.23 A3 cell volume with 40.29 nm crystal size and density Ï = 6.95 g / cm3 with x-ray diffraction measurements as a result. Specification phase as a resukt of qualitative analysis and crystal size as a result of quantitaive analysis explained that the substitution can be done. Keywords: perovskite manganites, mechanical alloying, High Energy Ball Mill, X-ray Diffraction, Monoclinic.